2012
DOI: 10.1371/journal.pone.0036163
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Mesenchymal Stem Cell Immunogenicity through Forced Expression of Human Cytomegalovirus US Proteins

Abstract: BackgroundMesenchymal stem cells (MSC) are promising candidates for cell therapy, as they migrate to areas of injury, differentiate into a broad range of specialized cells, and have immunomodulatory properties. However, MSC are not invisible to the recipient's immune system, and upon in vivo administration, allogeneic MSC are able to trigger immune responses, resulting in rejection of the transplanted cells, precluding their full therapeutic potential. Human cytomegalovirus (HCMV) has developed several strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…However, the mechanism of hMSC evasion from NK cells was not fully elucidated. These engineered hMSCs, after injection into the liver of pre-immune fetal sheep, were less susceptible to NK cell–mediated lysis and had a 1.8-fold increase in engraftment (in terms of percent of donor cells found in the liver 66 days after injection) compared to unmodified hMSCs 94 . Whether these virus-inspired strategies will prevent immune memory in a fully immune-competent host or enhance the therapeutic effect of MSCs in disease models remains to be determined.…”
Section: Strategies To Prolong Msc Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of hMSC evasion from NK cells was not fully elucidated. These engineered hMSCs, after injection into the liver of pre-immune fetal sheep, were less susceptible to NK cell–mediated lysis and had a 1.8-fold increase in engraftment (in terms of percent of donor cells found in the liver 66 days after injection) compared to unmodified hMSCs 94 . Whether these virus-inspired strategies will prevent immune memory in a fully immune-competent host or enhance the therapeutic effect of MSCs in disease models remains to be determined.…”
Section: Strategies To Prolong Msc Persistencementioning
confidence: 99%
“…However MSC immune evasion was achieved only after NK cell depletion, as the lack of MHC class I expression made hMSCs susceptible to ‘missing self ’ NK cell-mediated lysis 93 . Soland et al also infected hMSCs with immunoevasins from HCMV 94 (US2, US3, US6 or US11). Expression of either US6 or US11 resulted in significant suppression of MHC class I surface expression, and facilitated hMSC evasion of recognition by cytotoxic lymphocytes.…”
Section: Strategies To Prolong Msc Persistencementioning
confidence: 99%
“…In addition, since MSC, despite their immunomodulatory properties, can still be a target of activated NK 14-16 and cytotoxic T cells, 15 it is possible that overexpression of HLA-G1 could lead to increased survival of MSC after infusion. 17 Therefore, here we investigated which gene transfer system is best suited for delivering this molecule while maintaining its immunomodulatory effect by performing a side-by-side comparison between a lentiviral vector (Lv-HLA-G1), a murine retroviral vector (Rv-HLA-G1), and three nonviral plasmid constructs including a conventional plasmid (pmax-HLA-G1), a minicircle (MC-HLA-G1), and an episomal plasmid (pEP-HLAG1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HCMV has been shown to up-regulate the host-encoded CD55 and CD46 after infection of human fibroblasts [15]. We and others have previously shown that genetically engineering mesenchymal, and other cell populations, with retroviral vectors encoding HCMV proteins US2, US3, US6, and US11 down-modulated HLA-I expression [16], [17], [18], leading to a decrease in allogeneic cytotoxic T lymphocyte (CTL) activation and natural killer cell (NK) killing [19]. In this study, we investigated the role of the HCMV US proteins US2, 3, 6 and 11 in protecting MSC from complement lysis, and demonstrated that different US proteins up-regulate the expression of complement regulatory proteins at different levels, but that overexpression of US2 protein on MSC enhanced the production of all of the complement regulatory molecules expressed on these cells.…”
Section: Introductionmentioning
confidence: 99%